2009
DOI: 10.1096/fj.08-117739
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the murine receptor for advanced glycation end‐products (RAGE) gene

Abstract: The alternative splicing of pre-mRNAs is a critical mechanism in genomic complexity, disease, and development. Studies of the receptor for advanced glycation end-products (RAGE) indicate that this gene undergoes a variety of splice events in humans. However, no studies have extensively analyzed the tissue distribution in other species or compared evolutionary differences of RAGE isoforms. Because the majority of studies probing RAGE function have been performed in murine models, we therefore performed studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
109
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 41 publications
9
109
2
Order By: Relevance
“…While diabetic mice demonstrated a significant increase in RAGE splice variants, the latter was not associated with any detectable level of sRAGE protein in murine plasma [23]. Since sRAGE can be readily detected in human plasma, this observation not only indicates important differences between human and murine RAGE [23], but further implies that sRAGE observed in humans is, in the main, produced by shedding mechanisms [49]. Since in vitro and experimental animal models have demonstrated that exogenous sRAGE functions as a decoy by preventing ligands from interacting with cellular RAGE, it was supposed that sRAGE might counteract RAGE-mediated cell activation [53].…”
Section: The Multiple Levels Of Regulation Of the Rage Pathwaymentioning
confidence: 80%
See 3 more Smart Citations
“…While diabetic mice demonstrated a significant increase in RAGE splice variants, the latter was not associated with any detectable level of sRAGE protein in murine plasma [23]. Since sRAGE can be readily detected in human plasma, this observation not only indicates important differences between human and murine RAGE [23], but further implies that sRAGE observed in humans is, in the main, produced by shedding mechanisms [49]. Since in vitro and experimental animal models have demonstrated that exogenous sRAGE functions as a decoy by preventing ligands from interacting with cellular RAGE, it was supposed that sRAGE might counteract RAGE-mediated cell activation [53].…”
Section: The Multiple Levels Of Regulation Of the Rage Pathwaymentioning
confidence: 80%
“…The quaternary structure of the RAGE extracellular domain, but also post-translational modifications of its primary structure, might account for the diversity of ligand recognition. It remains unknown whether differences in splice variants between humans and mice [23] might also influence ligand specificity in different diseases. Thus, the postulated promiscuity of RAGE, which would make it potentially able to bind almost damage-associated molecular patterns [24], does not in fact exist, since post-translational modifications affect the relative specificity of a given ligand in a given situation of cellular activation.…”
Section: The Multiple Levels Of Regulation Of the Rage Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The receptor for advanced glycation end products (RAGE) is a multiligand PRR that is expressed in all tissues and on a wide range of cell types, including renal mesangial cells, (proximal) tubuli, podocytes and Bowman's capsule [2][3][4][5][6] and mediates a variety of inflammatory responses in renal diseases [7] . RAGE blockade or deficiency has been shown to suppress hepatic, cardiac, lung and brain I/R-induced injury [8][9][10][11][12] ; however, the contribution of RAGE in renal I/R-induced injury is unknown [13] .…”
mentioning
confidence: 99%